Dynamic Characteristics of Explosive Damage to Typical Undersea Vehicles - Kan YAN (水下无人系统学报)
This study examined the explosive damage characteristics of large undersea vehicle structures, which are crucial for improving the survivability of undersea vehicles and have far-reaching influence on tactical application and strategic deployment in naval battle. Initially, the study utilized the structured arbitrary Lagrangian-Eulerian(S-ALE) model to create models for both an undersea vehicle and underwater explosion and analyzed the characteristics of bubble motion near the wall in underwater explosion. It then investigated the structural damage characteristics of the vehicle under the influence of underwater explosion shockwaves and bubble loads. The results reveal that hydrostatic pressure amplifies the damage inflicted by explosion. Furthermore, when the undersea vehicle is exposed to attacks from two explosive charges, a greater distance between the horizontally arranged explosion sources within a certain range results in a more severe damage to the vehicle.